The Quality of Inpatient Child Health Services at RSUD Dr. Doris Sylvanus Palangka Raya - Fransisko Fransisko; Asmu’i Asmu’i; Rahma Yuliani (Universitas Padjadjaran, 2021)
This study aims to identify the quality of child health services in the inpatient room, identifying and analyzing inhibiting and supporting factors for the quality of child health services at dr. Doris Sylvanus Hospital Palangka Raya. It is a qualitative descriptive study conducted by applying observation, interviews, and documentation to collect data. It involved 3 nurses at dr. Doris Sylvanus Hospital Palangka Raya and 11 families of child patients as research subjects. The research showed that the quality of inpatient child health services dr. Doris Sylvanus Palangka Raya Hospital, especially those in the flamboyant room can be said to be good and able to meet the satisfaction of patients reviewed from 3 elements of service quality refers to Haywood-farmer, namely: Physical Facilities and Processes, People's Behaviour, Professional Judgment. However, there are some patient complaints caused by several factors inhibiting the quality of service at dr. Doris Sylvanus Hospital reviewed the quality of service elements referring to Haywood-farmer, namely: Physical Facilities and Processes, and Professional Judgment.